Pengaruh Objek Wisata Halal, Lama Usaha, Modal, dan Kunjungan Wisatawan Terhadap Pendapatan Pedagang di Kawasan Wisata Gentala Arasy Kota Jambi - Muhammad Ridel Fiandry; Titin Agustin Nengsih; Angger Hidayat (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to determine the influence of halal tourist attractions, length of business, capital and tourist visits on traders' income in the Gentala Arasi tourist area, Jambi City. The number of samples in this study was 64 people and used a simple random sampling technique, namely accidental sampling by selecting random samples that were accidentally encountered. Multiple Regression Analysis is used as a data analysis technique. The research results show that halal tourist attractions and tourist visits have a significant effect on traders' income, while length of business and capital do not have a significant effect. Based on data analysis in this research, these variables are valid and reliable. When testing classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occur.